ChemInform Abstract: [1, 4]‐S‐ to O‐Silyl Migration: Multicomponent Synthesis of α‐Thioketones Through Chemoselective Transformation of Esters to Ketones with Organolithium Reagents. Issue 21 (27th May 2014) - Sun, Xianwei; Song, Zhenlei; Li, Hongze; Sun, Changzheng
Abstract The three epoxide derivatives show different selectivities [(IIIg), (V), (VII)].